Motivation Learning English During Pandemic - Adisty Aryani; Nazriani Lubis; Azhary Tambusai; Melly Lestari (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2021)
This study aims to determine the perception of EFL students towards learning English during the COVID-19 pandemic at SMKN 3 Medan. The data collection is done through interviews. There were 6 students of grade XI APL 4 participating in this study. Since this research has explored students’ perception and motivation derived from students’ experiences during distance studying carried out due to the covid-19 pandemic. Descriptive research using qualitative technique is considered the right approach. The results of this study are presented descriptively to reveal students’ perception and motivation comprehensively. The result found that E-Learning got a bad perception because it was flexible and ineffective.